Effect of sacubitril/valsartan on investigator‐reported ventricular arrhythmias in PARADIGM‐HF. (19th January 2022) - Curtain, James P.; Jackson, Alice M.; Shen, Li; Jhund, Pardeep S.; Docherty, Kieran F.; Petrie, Mark C.; Castagno, Davide; Desai, Akshay S.; Rohde, Luis E.; Lefkowitz, Martin P.; Rouleau, Jean‐Lucien; Zile, Michael R.; et al.
Abstract : Aims: Sudden death is a leading cause of mortality in heart failure with reduced ejection fraction (HFrEF). In PARADIGM‐HF, sacubitril/valsartan reduced the incidence of sudden death. The purpose of this post hoc study was to analyse the effect of sacubitril/valsartan, compared to enalapril, on the incidence of ventricular arrhythmias. Methods and results: Adverse event reports related to ventricular arrhythmias were examined in PARADIGM‐HF. The effect of randomized treatment on two arrhythmia outcomes was analysed: ventricular arrhythmias and the composite of a ventricular arrhythmia, implantable cardioverter defibrillator (ICD) shock or resuscitated cardiac arrest. The risk of death related to a ventricular arrhythmia was examined in time‐updated models. The interaction between heart failure aetiology, or baseline ICD/cardiac resynchronization therapy‐defibrillator (CRT‐D) use, and the effect of sacubitril/valsartan was analysed. Of the 8399 participants, 333 (4.0%) reported a ventricular arrhythmia and 372 (4.4%) the composite arrhythmia outcome. Ventricular arrhythmias were associated with higher mortality. Compared with enalapril, sacubitril/valsartan reduced the risk of a ventricular arrhythmia (hazard ratio [HR] 0.76, 95% confidence interval [CI] 0.62–0.95; p  = 0.015) and the composite arrhythmia outcome (HR 0.79, 95% CI 0.65–0.97; p  = 0.025). The treatment effect was maintained after adjustment and accounting for the competing risk of death. Baseline ICD/CRT‐D use did not modify the effect of sacubitril/valsartan, but aetiology did: HR in patients with an ischaemic aetiology 0.93 (95% CI 0.71–1.21) versus 0.53 (95% CI 0.37–0.78) in those without an ischaemic aetiology ( p for interaction = 0.020). Conclusions: Sacubitril/valsartan reduced the incidence of investigator‐reported ventricular arrhythmias in patients with HFrEF. This effect may have been greater in patients with a non‐ischaemic aetiology. Abstract : PARADIGM‐HF trial design and main findings. HFrEF, heart failure with reduced ejection fraction; HR, hazard ratio.